2019
DOI: 10.1002/adom.201900661
|View full text |Cite
|
Sign up to set email alerts
|

Direct Light‐Writing of Nanoparticle‐Based Metallo‐Dielectric Optical Waveguide Arrays Over Silicon Solar Cells for Wide‐Angle Light Collecting Modules

Abstract: Here presented are the properties and performance of a new metallo‐dielectric waveguide array structure as the encapsulation material for silicon solar cells. The arrays are produced through light‐induced self‐writing combined with in situ photochemical synthesis of silver nanoparticles. Each waveguide comprises a cylindrical core consisting of a high refractive index polymer and silver nanoparticles homogenously dispersed in its medium, all of which are surrounded by a low refractive index common cladding. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 26 publications
(26 reference statements)
0
24
0
Order By: Relevance
“…Previous studies have shown that photopolymer nanoparticle formulations can undergo self-trapping, , with the presence of the nanoparticles not being deleterious to the process. Our recent work on the in situ production of nanoparticles in filaments is also a step in this general direction …”
Section: Recent Work On Self-trapping and Self-writing Polymer Materialsmentioning
confidence: 93%
See 4 more Smart Citations
“…Previous studies have shown that photopolymer nanoparticle formulations can undergo self-trapping, , with the presence of the nanoparticles not being deleterious to the process. Our recent work on the in situ production of nanoparticles in filaments is also a step in this general direction …”
Section: Recent Work On Self-trapping and Self-writing Polymer Materialsmentioning
confidence: 93%
“…These advances have included the concurrent self-trapping of multiple microscale beams in different photoinitiated media, as well as self-trapping in different polymeric media, such as blends and photopolymer–solvent mixtures. This has led to an understanding of the underlying photopolymer reaction kinetics, diffusion, and dynamics and the resultant structures, which are discussed herein, as well as a range of functional applications, , whose in-depth discussion is beyond the scope of this perspective.…”
Section: Recent Work On Self-trapping and Self-writing Polymer Materialsmentioning
confidence: 99%
See 3 more Smart Citations